Postdischarge antibiotic use for prophylaxis following spinal fusion. (5th July 2020) - Warren, David K.; Nickel, Katelin B.; Han, Jennifer H.; Tolomeo, Pam; Hostler, Christopher J.; Foy, Katherine; Banks, Ian R.; Fraser, Victoria J.; Olsen, Margaret A.; ,
Abstract: Objective: Despite recommendations to discontinue prophylactic antibiotics after incision closure or <24 hours after surgery, prophylactic antibiotics are continued after discharge by some clinicians. The objective of this study was to determine the prevalence and factors associated with postdischarge prophylactic antibiotic use after spinal fusion. Design: Multicenter retrospective cohort study. Patients: This study included patients aged ≥18 years undergoing spinal fusion or refusion between July 2011 and June 2015 at 3 sites. Patients with an infection during the surgical admission were excluded. Methods: Prophylactic antibiotics were identified at discharge. Factors associated with postdischarge prophylactic antibiotic use were identified using hierarchical generalized linear models. Results: In total, 8, 652 spinal fusion admissions were included. Antibiotics were prescribed at discharge in 289 admissions (3.3%). The most commonly prescribed antibiotics were trimethoprim/sulfamethoxazole (22.1%), cephalexin (18.8%), and ciprofloxacin (17.1%). Adjusted for study site, significant factors associated with prophylactic discharge antibiotics included American Society of Anesthesiologists (ASA) class ≥3 (odds ratio [OR], 1.31; 95% CI, 1.00–1.70), lymphoma (OR, 2.57; 95% CI, 1.11–5.98), solid tumor (OR, 3.63; 95% CI, 1.62–8.14), morbid obesity (OR, 1.64; 95% CI, 1.09–2.47), paralysis (OR, 2.38; 95% CI, 1.30–4.37), hematoma/seroma (OR, 2.93; 95% CI, 1.17–7.33), thoracic surgery (OR, 1.39; 95% CI, 1.01–1.93), longer length of stay, and intraoperative antibiotics. Conclusions: Postdischarge prophylactic antibiotics were uncommon after spinal fusion. Patient and perioperative factors were associated with continuation of prophylactic antibiotics after hospital discharge.